2017
DOI: 10.1590/s0100-204x2017001200011
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic content and antioxidant activity of fruit of Brazilian genotypes of feijoa

Abstract: -The objective of this work was to quantify the total phenolic content (TPC) and total antioxidant activity (TAA) of fruit from Brazilian genotypes of feijoa (Acca sellowiana). Skin and flesh tissues of the fruit were evaluated for the Alcântara, Helena, Mattos, and Nonante cultivars, and for the 2316 accession. TPC and TAA were both assessed in aqueous and hydroalcoholic extracts, and TAA was assayed by the DPPH (2,2-diphenyl-1-picrylhydrazyl) and ABTS [2,2'-azino-bis(3-ethylbenzothiazoline-6-sulphonic acid)]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
2
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 23 publications
1
21
2
1
Order By: Relevance
“…The procedure to obtain the hydroalcoholic extract for quantification of TPC and TAA was described by Amarante et al (2017b). TPC [mg gallic acid equivalents (GAE) 100 g -1 FM] was quantified using the Folin-Ciocalteu method, and TAA was determined based on the ability of the extract to scavenge the radicals ABTS [2,2'-azino-bis (3-ethylbenzothiazoline-6-sulphonic acid)] and DPPH (1,1-diphenyl-2-picrylhydrazyl), as described by Amarante et al (2017b). TAA was expressed as Trolox equivalent antioxidant capacity (TEAC, μmol Trolox g -1 FW) for ABTS method, and as EC 50 (substrate concentration which leads to 50% reduction of DPPH, determined as mg FW g -1 DPPH) for DPPH method.…”
mentioning
confidence: 99%
“…The procedure to obtain the hydroalcoholic extract for quantification of TPC and TAA was described by Amarante et al (2017b). TPC [mg gallic acid equivalents (GAE) 100 g -1 FM] was quantified using the Folin-Ciocalteu method, and TAA was determined based on the ability of the extract to scavenge the radicals ABTS [2,2'-azino-bis (3-ethylbenzothiazoline-6-sulphonic acid)] and DPPH (1,1-diphenyl-2-picrylhydrazyl), as described by Amarante et al (2017b). TAA was expressed as Trolox equivalent antioxidant capacity (TEAC, μmol Trolox g -1 FW) for ABTS method, and as EC 50 (substrate concentration which leads to 50% reduction of DPPH, determined as mg FW g -1 DPPH) for DPPH method.…”
mentioning
confidence: 99%
“…Similarly, Peng et al (2019) reported that antioxidant activity of New Zealand grown feijoa peel extracts were significantly higher than the whole fruit and flesh extracts. Amarante et al (2017) reported that the feijoa peel extracts exhibited stronger antioxidant activity than the flesh extracts. In the present study, it was observed that antioxidant activity of the feijoa extracts increased with increasing the concentration of extracts and DPPH radical scavenging activity of 5% extracts were higher than 2.5% extracts.…”
Section: Antioxidant Activitymentioning
confidence: 99%
“…For polyphenols, phenolic acids and flavonoids (e.g., flavone, catechin, quercetin-glycoside, procyanidin B1 and B2) have been found and identified as the major phenolic compounds in the feijoa fruits [4,5,6]. Interestingly, the bioactive components are not only present in the pulp, but also found at a relatively high level in the other biological tissues of the plant such as peel, leaf and flower bud [6,7,8,9]. Although the feijoa fruit peel is edible and can be a rich source of functional ingredients such as polyphenols and pectin fibre [4], it is considered as a by-product of food processing.…”
Section: Introductionmentioning
confidence: 99%